Language attitudes and habits among students of the Bachelor’s Degree in Early Childhood Education (UIB) - Calafat Vila, Rosa; Calero-Pons, Àlvaro (Didáctica. Lengua y Literatura, 2019)
When acquiring a language, pragmatic competence becomes essential, given that positive attitudes and habits towards the environment have to be derived from its knowledge. This fact assumes a particular relevance when it comes to learning a minoritized language, which is forced to share functions with other language having more symbolic weight. In this paper, we analyze the linguistic perceptions of one of three first year groups which have taken the subject Catalan Language and its Teaching, from the Bachelor’s Degree in Early Childhood Education at University of the Balearic Islands (UIB), in the first four months of the school year 2017-2018. We intend to confirm the correlation between favorable attitudes and habits towards Catalan with the curricular learning objectives. Beyond the linguistic policies which are applied to the normalization of Catalan in the Balearic university teaching, the influence of environment determines the students’ linguistic performance.